Lines in the Mud: Tank Eco-restoration and Boundary Contestations in Chennai. (November 2020) - Coelho, Karen
This article analyses the politics of environmentalism revealed in struggles over the land–water boundary of an urbanising tank in Chennai. In contesting this boundary, property-less settlers on its banks called into question the tank's 'nature' and functions in its urban milieu, and demanded a redrawing of boundaries to reflect the socio-natural transformations that had turned parts of it into land. Simultaneously, propertied residents, in concert with state eco-restoration schemes and court rulings, fought to restore the tank to its 'original' dimensions. In foregrounding the liminalities of the urbanising tank, this article suggests the limits of the contemporary property-determined eco-restoration discourse, premised on a return to pristine pasts and original boundaries. It proposes that the stand-off between water body restoration and the defence of working-class housing rights necessitates recognising the tank as an artefact assembled over time by socio-technical and natural processes.